2011
DOI: 10.5455/vetworld.2011.124-125
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and Biochemical changes of stunting syndrome in Broiler chicken

Abstract: An experiment was carried out to study the hematological and biochemical changes of stunting syndrome in broiler chicken from day old ( group I) and 3 weeks (group III) of age to 8 weeks of age in two phases along with group II and group IV as control. Birds were slaughtered at 3, 5 ,7 and 8 weeks of age and the blood samples were collected and analyzed. The mean PCV, Hb, TEC values were reduced significantly (P<0.01) in stunted birds. Increased AHC, AMC and ABC values along with decreased ALC values were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
3
10
1
Order By: Relevance
“…Generally leucocytes perform their appropriate functions in specific tissues and use the blood just as a vehicle for transit between site of formation, activity and storage. The values for total leucocyte count as obtained in present study were significantly higher than normal are in agreement with the studies of Rani et al (2011). The increase in WBCs could be due to many reasons including stress and infection (Otto et al, 2006).…”
Section: Absolute Eosinophil Count (Aec)supporting
confidence: 91%
See 4 more Smart Citations
“…Generally leucocytes perform their appropriate functions in specific tissues and use the blood just as a vehicle for transit between site of formation, activity and storage. The values for total leucocyte count as obtained in present study were significantly higher than normal are in agreement with the studies of Rani et al (2011). The increase in WBCs could be due to many reasons including stress and infection (Otto et al, 2006).…”
Section: Absolute Eosinophil Count (Aec)supporting
confidence: 91%
“…If haemoglobin concentration of red blood cells is below the standard limit then anaemia is considered to be present (Turgeon, 1999). These results were found similar to the finding of Rani et al (2011) who found the decreased values of Hb and TEC and relate them with anaemic changes caused by malabsorption syndrome.…”
Section: Absolute Eosinophil Count (Aec)supporting
confidence: 91%
See 3 more Smart Citations